The gland factory : a tour of your body's goops, juices, and hormones - Poliquin, Rachel, 1975- (Greystone Kids, 2025)
"From the award-winning creators of The Museum of Odd Body Leftovers, comes a wonderfully fun--sometimes gross--exploration of the endocrine and exocrine systems. A perfect book for engaging kids ages 8-12 in STEM. Step right up for a tour of one incredible factory--a fascinating system inside your body! The human body is all kinds of amazing. Inside you, systems are working hard to make sure your heart doesn't beat too fast or too slow, you aren't too hot or too cold, and you don't fall asleep on your desk at school (most of the time, anyways). No matter what you do, your body tends to exist in a state of balance. In fact, a happy, healthy life depends on that balance. And that balance depends on glands. In The Gland Factory, you'll get an up-close look at your endocrine and exocrine systems, where glands are feverishly swelling, shrinking, oozing, healing, digesting, and maintaining balance. Extensive backmatter includes a suggested further reading list, a 'Gland Factory Survey' and a detailed glossary of all the wonderfully gross glands explored. Each stop on the tour introduces fascinating facts about how some key glands and hormones work, including: The Mouth Machine (the salivary glands); The Sugar Boss (the pancreas); The Main Control (the hypothalamus). When the factory is infiltrated by nasty germs, the immune system springs into action, fighting hard to restore order. A little weird, a little gross, and more than a little fun, The Gland Factory is an unforgettable exploration of the human body!"--